2020
DOI: 10.4317/medoral.23729
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunohistochemical epithelial profile of non-healing chronic traumatic ulcers

Abstract: Background Chronic wounds were previously related to cancer. Chronic Traumatic Ulcers (CTU) are lesions caused by chronic mechanical irritation (CMI) frequently diagnosed in Oral Medicine. Although these conditions may reflect a benign nature, some authors have proposed its relationship with malignant transformation. Currently, there are scarce investigations that evaluate biomarkers within CTU. The aim of this study was to evaluate cell differentiation and proliferation biomarkers patterns of CTU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
1
11
1
2
Order By: Relevance
“…9 Consequently, OSCC arises most frequently in high-risk areas such as the ventrolateral tongue and the floor of the mouth. 10 However these kind of lesions could also be seen in vestibular sulcus, buccal mucosa and alveolar ridge as happened in our case. 11,12 Clinically, OSCC can be seen in different forms ranging from white plaque to ulcers.…”
Section: Discussionsupporting
confidence: 57%
“…9 Consequently, OSCC arises most frequently in high-risk areas such as the ventrolateral tongue and the floor of the mouth. 10 However these kind of lesions could also be seen in vestibular sulcus, buccal mucosa and alveolar ridge as happened in our case. 11,12 Clinically, OSCC can be seen in different forms ranging from white plaque to ulcers.…”
Section: Discussionsupporting
confidence: 57%
“…Even, without being mutagenic, CMI could generate conditions that could facilitate initiation. Gilligan et al in their cross-sectional study have reported that several specimens of CTU expressed altered immunohistochemical pattern similar to OSCC thereby confirming the role of CMI in oncogenesis [ 47 ]. Studies done on the experimental animal model showed that when combined with chronic trauma, a relatively lower dose of 7,12-dimethyl-benzanthracene (DMBA) was sufficient to induce carcinogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…Receptors from the family of integrins and syndecans are usually overexpressed when the epithelium is exposed to mechanical trauma 32 . CMI generates a hyperproliferative status of the oral epithelium, increasing the persistence, even in suprabasal strata, of immature cells (immunolabelled with cytokeratins 19) with an immunohistochemical pattern similar to basal keratinocytes 33 . This phenomenon linked to CMI could facilitate the persistence and the viral infection of the oral mucosa.…”
Section: Discussionmentioning
confidence: 99%